Multi–detector CT Urography in the diagnosis of urinary tract abnormalities - Rajesh Gupta; S Raghuvanshi (International Journal of Medical Research and Review, 2016)
Introduction: Different imaging techniques are being used in the diagnosis of urinary tract abnormalities. IVU, magnetic resonance (MR) imaging, ultrasonography (US), computed tomography (CT), retrograde ureterography, pyelography, cystoscopy, and ureteroscopy are used to diagnose patients with urinary complaints. Non contrast MDCT is now routinely used to evaluate calculi, Renal masses, ureteral abnormalities and urinary bladder masses. Excretory-phase CT can now be used to evaluate the ureter. Preliminary results of excretory-phase CT demonstrate a high sensitivity (95%) in diagnosing upper urinary tract uroepithelial malignancy. CT usually demonstrates bladder disease, but flat tumours of the bladder are difficult to be identified with CT, and the cystoscopy remains the study of choice in evaluating for bladder malignany. Now with the help of MDCT protocol, comprehensive evaluation of renal disease can be performed.Material and Methods: It is a retrospective study of 60 patients, From May 2013 to November 2014. 60 patients (41 male and 19 were females with mean age 44 yrs (age range 27 – 61 years) were selected in this study. All the patients underwent CT scan study with or without intravenous contrast medium. CT scan study was performed on a MDCT scanner (Siemens Medical Systems).Result: Out of 60 patients, 42 (70 %) had urolithiasis. The unenhanced CT examination provides adequate information of all urinary calculi and associated hydronephrosis. 18 cases (30 %) demonstrated non urolithiasis abnormality. Out of 18 cases, 6 (10 %) cases demonstrated masse, 8 (13.33 %) cases demonstrated inflammatory changes. Congenital anomalieswas found in 4 patients (6.66%).Conclusion: MDCT urography is the best modality with a combination of unenhanced, nephrographic-phase and excretory-phase in wide spectrum of urinary tract abnormalities. CT urography demonstrates both intrinsic and extrinsic abnormalities of ureter than IVU.